2020
DOI: 10.3389/fpls.2020.581100
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Plant Production of Recombinant NS1 Protein for Diagnosis of Dengue

Abstract: Dengue fever is endemic in more than 120 countries, which account for 3.9 billion people at risk of infection worldwide. The absence of a vaccine with effective protection against the four serotypes of this virus makes differential molecular diagnosis the key step for the correct treatment of the disease. Rapid and efficient diagnosis prevents progression to a more severe stage of this disease. Currently, the limiting factor in the manufacture of dengue (DENV) diagnostic kits is the lack of large-scale product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Our results were superior or equivalent to those of commercially available tests previously reported in the literature, including the Panbio Dengue virus IgG Capture ELISA (56% sensitivity and 95% specificity) and the SD Bioline Dengue IgG ELISA (89% sensitivity and 64% specificity) [ 10 ]. Regarding experimental tests, we achieved comparable performance to tests based on full-length DENV NS1 proteins, such as the DENV-1–4 NS1 IgG ELISA (83–87% sensitivity, 81–93% specificity) [ 29 ], the DENV2 NS1 IgG ELISA (83% sensitivity and 88% specificity) [ 30 ]. Although envelope-based tests showed greater specificity than the T-ΔNS1-based DENV IgG ELISA [ 31 ], studies conducted before the ZIKV outbreak did not encounter cross-reactivity issues between DENV and ZIKV.…”
Section: Discussionmentioning
confidence: 96%
“…Our results were superior or equivalent to those of commercially available tests previously reported in the literature, including the Panbio Dengue virus IgG Capture ELISA (56% sensitivity and 95% specificity) and the SD Bioline Dengue IgG ELISA (89% sensitivity and 64% specificity) [ 10 ]. Regarding experimental tests, we achieved comparable performance to tests based on full-length DENV NS1 proteins, such as the DENV-1–4 NS1 IgG ELISA (83–87% sensitivity, 81–93% specificity) [ 29 ], the DENV2 NS1 IgG ELISA (83% sensitivity and 88% specificity) [ 30 ]. Although envelope-based tests showed greater specificity than the T-ΔNS1-based DENV IgG ELISA [ 31 ], studies conducted before the ZIKV outbreak did not encounter cross-reactivity issues between DENV and ZIKV.…”
Section: Discussionmentioning
confidence: 96%
“…Thus far, many studies have confirmed the plants' potential to produce enzymes, antimicrobial peptides, antibodies, viral proteins, and many other molecules. [107][108][109][110][111][112][113][114] 115 To date, there are 109 transgenic plants approved for use in the European Union, most of them being used as animal feed ingredients. 116 These plants or their products are mostly imported from North and South America, not grown in the European Union, where only a few approvals were issued.…”
Section: Molecular Farming Of Fish Vaccinesmentioning
confidence: 99%
“…Plant‐based production of proteins with their subsequent application in the pharmaceutical, veterinary, or agriculture industry is referred to as “molecular farming”. Thus far, many studies have confirmed the plants' potential to produce enzymes, antimicrobial peptides, antibodies, viral proteins, and many other molecules 107–114 . Although it may not be possible to generalize, compared to other commonly used expression systems, such as bacterial, yeast, or animal cells, plant‐based production offers solutions superior in terms of total yield, price, and proper protein folding while providing a natural encapsulation allowing delivery of the antigens into the inductive sites without additional processing.…”
Section: Molecular Farming Of Fish Vaccinesmentioning
confidence: 99%
“…Detection of anti-dengue antibodies is complicated by the absence of large-scale production of the dengue virus non-structural 1 (NS-1) protein to be used in capturing antibodies from the blood serum of dengue patients. Xisto et al, 2020 [ 248 ] expressed the NS1 protein of the dengue virus serotype 2 (NS1DENV2) using transgenic Arabidopsis thaliana wherein 203 mg of the recombinant NS1 protein was obtained per gram of fresh leaf material. This plant-produced antigen exhibited high specificity and sensitivity to both IgM and IgG.…”
Section: Other Plant-based Vaccinesmentioning
confidence: 99%